Transcriptome Responses to Dexamethasone Depending on Dose and Glucocorticoid Receptor Sensitivity in the Liver - Murani, Eduard; Trakooljul, Nares; Hadlich, Frieder; Ponsuksili, Siriluck; Wimmers, Klaus (Frontiers in Genetics, 2019)
Tissue sensitivity to glucocorticoids is a key factor dictating outcome of their homeostatic and therapeutic action, whereby liver represents one of the major peripheral targets. Here, we used pigs carrying a natural gain-of-function glucocorticoid receptor variant Ala610Val (GRAla610Val) as a model to identify genes and pathways related to differential glucocorticoid sensitivity. Animals with different GRAla610Val genotypes were treated either with saline or two different doses of dexamethasone. Genome-wide transcriptional responses depending on treatment, genotype, and their interaction in the liver were investigated using mRNA sequencing. Dexamethasone induced vast transcriptional responses, with more than 30% of present genes being affected. Functional annotation of genes differentially expressed due to dexamethasone treatment suggested that genes related to inflammation respond more sensitively, despite absence of an immune stimulus. In contrast, genes involved in glucose metabolism and cancer appeared to be less sensitive. Analysis of genotype and genotype×treatment interaction revealed that clustered protocadherins, particularly PCDHB7, are most prominently affected by GRAla610Val, mainly depending on dose. GRAla610Val influenced also expression of a set of glucose metabolism related genes, including PPARGC1A and CEBPB, in the absence of dexamethasone though no differences in basal plasma glucose level were observed. This might represent an adaptive response, keeping balance between receptor sensitivity and level of circulating endogenous glucocorticoids. Administration of low dexamethasone dose changed their expression pattern and induced higher glucose response in carriers of the hypersensitive Val receptor. Our findings suggest that GRAla610Val modulates tissue responses to glucocorticoids dynamically, depending on their circulating level.